The Effect of Dividend Policy on Share Price Volatility of Some Selected Companies on the Nigerian Exchange - Koleosho, Adekunle Orelope; Akintoye, Ishola Rufus; Ajibade, Ayodeji Temitope (Journal of Accounting, Business and Finance Research, 2022)
Share price volatility has exhibited different patterns in different global exchange markets, including the Nigerian Exchange (NGX). Various attempts have been made to determine the possible causes of this volatility and how they can be mitigated, but there have been fewer studies in this regard, especially in developing economies such as Nigeria. Hence, this study examines the effect of dividend policy on share price volatility of selected companies listed on the NGX. The study adopted an ex-post facto research design and used the EGARCH to measure volatility. A sample of 49 of 162 companies listed on the Nigerian Exchange during the study period (2010–2020) was randomly selected for the panel data. The study found that the dividend policy has a significant relationship with share price volatility (SPV), with an adjusted R2 value of 0.116, a Wald (3, 2156) value of 32.89, and a p-value of 0.000. The dividend payout ratio (DPR) has a significant effect on SPV (DPR = 0.0036, t(2156) = 4.7237, p < 0.05); dividend yield (DY), dividend per share (DPS) and financial leverage (LEV) have a negative insignificant effect on SPV (DY = -0.0003, t(2156) = -2.713, p > 0.05; DPS = -0.0508, t-test = -1.8952, p > 0.05; and LEV = -0.2066, t-test = -1.4742, p > 0.05, respectively). The study concludes that dividend policy has a significant effect on share price volatility. Based on the results, it is recommended that companies should focus more on payouts, while investors should opt for corporate entities with a constant payout ratio.